Efficient Coordination Among Chinese Provinces in Managing Supply and Demand for Staple Crops - Yifei Wang; Xiangzheng Deng; Yansui Liu; Juanle Wang; Zhihui Li (Food and Energy Security)
ABSTRACT Ensuring a stable supply and demand of food represents a pivotal challenge for sustainable development. This study seeks to delineate the spatiotemporal distribution and circulation patterns of supply and demand for staple crops, identify the major producing and consuming zones in China, and investigate the drivers underpinning efficient coordination of food supply and demand. Results indicate that between 2000 and 2020, China's food supply and demand expanded by 73.8% and 36.62%, respectively, achieving a supply surplus. However, the most significant threats to supply–demand coordination are the extensive use of feed and industrial crops, compounded by the import vulnerabilities arising from global supply chain uncertainties. In terms of major producing and consuming zones, Northeast China plays a vital role in the national food supply, contributing 71% of domestic soybeans, 55% of its maize, and 34% of its rice. Climatic conditions and self‐sufficiency rates are key determinants of provincial supply and demand for staple crops. Provinces such as Sichuan, Hubei, Anhui, and Shandong represent balanced producing–consuming zones for these staple crops. To enhance food supply–demand coordination, tailored and adaptive measures for different provinces are imperative. This study offers theoretical insights to understand the trends of food supply and demand and further contributes to adaptive strategies to address climate change for sustainable food systems.